Pedagogikalıq kommunikativ mádeniyatı bolajaq oqıtıwshınıń kásiplik tayarlıǵın jetilistiriwdiń shárti sıpatında (SCIENCE and SOCIETY, 2022)
This article states about the formation and improvement of a pedagogical communicative culture of future teachers with students in the process of communication and learning.